Interview with Dr. Betty Reardon on the Theme of Peace Education (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
The article, an interview with Dr. Betty Reardon on the theme of Peace Education, was conducted shortly after the 2000 International Institute of Peace Education (IIPE) in Pune, India, concluded in July of that year.  Dr. Reardon’s message however, seems as relevant today as it was when recorded a quarter century ago.
Keywords: Peace Education